Poly(Styrene Sulfonate-Co-Glycidyl Methacrylate)/Rhodamine B Films with Enhanced Energy Conversion in Luminescent Solar Concentrators Triggered by Aromatic-Aromatic Interactions - Melo-Hurtado, F (American Chemical Society, 2025)
Styrene sulfonate-glycidyl methacrylate copolymers have been rationally designed to furnish both insolubility in water and negatively charged aromatic functional groups that, upon undergoing aromatic-aromatic interactions with dyes, impart specific functionality to solid materials. Solid films incorporating varying amounts of the embedded fluorophore rhodamine B were obtained by solution casting of the copolymers onto glass substrates. The formed slabs were then evaluated for their potential use in energy conversion devices such as luminescent solar concentrators. The materials presented higher dye dispersion, avoiding nonfluorescent aggregates, increased fluorescence emission intensity, larger Stokes shift, lower absorption and emission overlap, reduced reabsorption, and longer fluorescence lifetime, compared with matrices made of rhodamine B/poly(methyl methacrylate). The higher dispersion, polarity, and charge transfer character in the excited state are claimed as the cause of these photophysical properties produced by the functional polymers. Tested in luminescent solar concentrator devices of 50 × 50 × 4 mm3, the device efficiency obtained reached 1.19%, whereas control devices made with rhodamine B/poly(methyl methacrylate) matrices only reached 0.33%. This aims at functional polymers containing aromatic charged residues in the solid state as potential tools to achieve improved performance in energy conversion devices based on the modulation of the photophysical response of aromatic dyes by means of aromatic-aromatic interactions. © 2025 American Chemical Society.